O campo das grandes empresas da construção civil. Perspetiva teórica e análise relacional sobre o caso português (em 2012) - Pereira, Vergílio Borges (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
This article discusses the relevance of an analytical approach inspired by Pierre Bourdieu's sociological theory of fields to understand the processes of structuring economic activity, focusing on the way in which such processes have been shaped in the construction sector in Portugal over the last two decades. By mobilising official statistical information on the social properties of the 200 largest construction companies in the country in 2012, this text attempts to provide a relational portrait of the forces that make up these companies and seeks to define the main implications that this has for the study of the space of social positions that they form.